Comparing the Therapeutic Potential of Stem Cells and their Secretory Products in Regenerative Medicine. (20th August 2021) - Foo, Jhi Biau; Looi, Qi Hao; Chong, Pan Pan; Hassan, Nur Hidayah; Yeo, Genieve Ee Chia; Ng, Chiew Yong; Koh, Benson; How, Chee Wun; Lee, Sau Har; Law, Jia Xian
Abstract : Cell therapy involves the transplantation of human cells to replace or repair the damaged tissues and modulate the mechanisms underlying disease initiation and progression in the body. Nowadays, many different types of cell-based therapy are developed and used to treat a variety of diseases. In the past decade, cell-free therapy has emerged as a novel approach in regenerative medicine after the discovery that the transplanted cells exerted their therapeutic effect mainly through the secretion of paracrine factors. More and more evidence showed that stem cell-derived secretome, i.e., growth factors, cytokines, and extracellular vesicles, can repair the injured tissues as effectively as the cells. This finding has spurred a new idea to employ secretome in regenerative medicine. Despite that, will cell-free therapy slowly replace cell therapy in the future? Or are these two modes of treatment still needed to address different diseases and conditions? This review provides an indepth discussion about the values of stem cells and secretome in regenerative medicine. In addition, the safety, efficacy, advantages, and disadvantages of using these two modes of treatment in regenerative medicine are also critically reviewed.